Penerapan Pajak Penghasilan (PPH) Final terhadap Usaha Mikro Kecil dan Menengah (UMKM) berdasarkan PP No 23 Tahun 2018 pada wilayah kerja Kantor Pelayanan Pajak Pratama Depok - Deddy Dariansyah (Neolectura, 2021)
With the issuance of Government Regulation (PP) Number 23 of 2018 concerning Final Taxes which are specifically applied to small and medium businesses and certain businesses, which have a gross income of IDR 4.8 billion in one year. The purpose of this study is the author wants to examine whether the application of Final Income Tax (PPh) with a tariff of 0.5% for Micro, Small and Medium Enterprises in Depok City is in accordance with Government Regulation No. 23 of 2018. The method used in this study is to analyze reports MSME finances as well as the application of the gross Final Income Tax on income for certain businesses in 2020. Based on financial reports from food and beverage distributors in 2020 from May to June there was an increase in income to coincide with the fasting month of Ramadan, after the end of July the income decreased again with the end of Eid al-Fitr, after analyzing and calculating based on financial reports, the income did not exceed Rp4,800,000,000 in one year. Taxpayers can get the final Income Tax rate on certain income category circulation.